THE APPLICATION OF SYNECTICS MODEL TO IMPROVE STUDENTS™SPEAKING ABILITY IN SENIOR HIGH SCHOOL - Tumangger, Masda; Ernidawati, Tjut (Universitas Negeri Medan, 2012)
This study deals with the application of synectics model to improve students™ speaking ability in senior high school. This reserach was conducted by applying Classroom Action Research with two cycles in six meetings. The subject of this study was a class in the second year students of SMA SWASTA NURUL HASANAH. There were 24 students that participated in this research. The The qualitative data were taken from the diary notes, interview sheet, observation sheet, and questionnaire sheet and the quantitative data was taken from the test result and done in a pre test and the two test. The result of of the quantitative data indicate that the score of the students imroved from cycle I to cycle II with a pre-test mean of 45.20, the test of cycle I was 46.79 and the test of cycle II was 77.83. The result of based on the data above, it can be concluded that the application of synectics model was significantly improved students™ speaking ability. Key words: Speaking, Synectics, test, data